TABERÎ’NİN TARİH ANLAYIŞI - Hasan Kurt (İslami İlimler Dergisi)
With his work Târîkh al-Rusul wa al-Muluk, al-Tabarî has become the best representative of the understanding of history in Islamic world from the very beginning until his time. Through al-Tabarî’s work, information found in many lost works has also reached, even if partly, at our time. In reporting historical accounts, al-Tabarî adopted a traditionalist method so that his reader could make a neutral assessment. In this context, he made some methodological attempts in such a way that he helped his readers make an assessment in their opinion. It seems that due to his oversensitivity of reliability the informative parts of his accounts in his work sometimes remained behind compared with the chain of narration. Al-Tabarî related the accounts from the creation of man to the migration of the Prophet Muhammad in accordance the subjects, while he recorded the events of the post-migration period in accordance with their chronological sequence. This may regarded as the lack of material at his disposal about the ancient nations and pre-migration period. Though his work largely shows the features of political history, there also exists information including social, religious, cultural economic etc. aspects. He also made use of such materials as poetry, letter and so on. This shows, though he did not compile a book for the methodology of history, that the understanding of historiography he pursued, when considered the conditions of that time, was never at a level that could be disregarded.